GREEN DIOPSIDE WITH MAUVE TERMINATION FROM THE BAZHENOVSKOE CHRYSOTILE-ASBESTOS DEPOSIT, CENTRAL URALS - V.A. Popov (Минералогия)
Some generations of diopside from rodingite (skarn?) veins of the Bazhenovskoe chrysotileasbestos deposit have complex crystallization evolution with the formation of zonal-sectorial polychrome crystals. The paper considers one example of diopside, the color of which is caused by Mn/Fe ratio in different elements of crystal anatomy. For example, the green color is typical of growth pyramids of faces {100}, {010}, {001}, {310}, whereas mauve color is observed in those of {831} and {22 1 }. The anatomy elements of red color exhibit maximum Mn contents.